Oxytocin Improves Follicular Reserve in a Cisplatin-Induced Gonadotoxicity Model in Rats. (14th May 2014) - Erbaş, Oytun; Akman, Levent; Yavaşoğlu, Altuğ; Terek, Mustafa Cosan; Akman, Tülay; Taskiran, Dilek
Abstract : Cisplatin (CP), an antitumor agent, has been shown to cause ovarian injury and dysfunction in both animal and human studies. The present study was conducted to investigate the protective effect of oxytocin (OT) on CP-induced ovarian toxicity in rats. Twenty-one adult female rats were included in the study. Fourteen rats were administered intraperitoneally CP (2 mg/kg/day) twice a week for 5 weeks. Control group (n = 7 ) did not receive any treatment. Following treatment, CP-received rats were randomly divided into two groups and treated with either saline (1 mL/kg/day, n = 7 ) or OT (160 μ g/kg/day, n = 7 ) for 5 weeks. Then, ovarian toxicity and effects of OT were evaluated by histomorphological and biochemical analysis. Our findings revealed a significant reduction in the number of follicles at each grade in saline-treated group. AMH level was significantly lower in saline group compared to control (P < 0.0005 ). OT treatment significantly attenuated CP toxicity in ovaries and increased AMH levels compared to saline group (P < 0.005 ). Also, administration of OT lessened lipid peroxidation and prevented glutathione depletion in CP-treated rats (P < 0.05 ). These results indicated that OT could lessen the CP-induced ovarian damage and improve follicular reserve by preventing oxidative damage.